Mechanistic models of α-synuclein homeostasis for Parkinson's disease: A blueprint for therapeutic intervention - Righetti, Elena; Antonello, Alice; Marchetti, Luca; Domenici, Enrico; Reali, Federico (Frontiers in Applied Mathematics and Statistics, 2022)
Parkinson's disease (PD) is the second most common neurodegenerative disorder worldwide, yet there is no disease-modifying therapy up to this date. The biological complexity underlying PD hampers the investigation of the principal contributors to its pathogenesis. In this context, mechanistic models grounded in molecular-level knowledge provide virtual labs to uncover the primary events triggering PD onset and progression and suggest promising therapeutic targets. Multiple modeling efforts in PD research have focused on the pathological role of α-synuclein, a presynaptic protein that emerges from the intricate molecular network as a crucial driver of neurodegeneration. Here, we collect the advances in mathematical modeling of αsyn homeostasis, focusing on aggregation and degradation pathways, and discussing potential modeling improvements and possible implications in PD therapeutic strategy design.